Compounds of Marine Origin with Possible Applications as Healing Agents - Nektaria-Ioanna Karma; Fotini Mellou; Panagoula Pavlou; Angeliki Siamidi; Athanasia Varvaresou (Marine Drugs)
It is well established that marine organisms consist of a great variety of active compounds that appear exclusively in the marine environment while having the ability to be vastly reproduced, irrespective of the existing conditions. As a result, marine organisms can be used in many scientific fields, including the ones of pharmaceutics, nutrition, and cosmetic science. As for the latter, marine ingredients have been successfully included in cosmetic formulations for many decades, providing numerous benefits for the skin. In the present review, the contribution of marine compounds in wound healing is thoroughly discussed, focusing on their role both as active ingredients in suitable formulations, designed to contribute to different stages of skin regeneration and restoration and also, indirectly, as a tool for facilitating wound closure as part of a wound dressing. Additionally, the advantages of these marine ingredients are presented, as well as ways of incorporating them effectively in formulations, so as to enhance their performance. Numerous studies have been referenced, showcasing their efficacy in wound healing. Finally, important data in regard to their stability, limitations, and challenges to their use, safety issues, and the existing legislative framework are extensively reviewed.